In vitro propagation, micromorphological studies and ex vitro rooting of cannon ball tree (Couroupita guianensis aubl.): a multipurpose threatened species - Shekhawat, Mahipal S. (Physiol Mol Biol Plants, 2016)
In vitro propagation methods using seeds and nodal segments of a 21-year old Couroupita guianensis - a medicinally important but threatened tree have been developed. Hundred percent of the seeds germinated on half strength Murashige and Skoog (MS) medium with 2.0 mg l(−1) indole-3 butyric acid (IBA). Nodal segments were found most suitable for the establishment of cultures. About 90 % explants responded and 4.1 ± 0.23 shoots per node were induced after five weeks of inoculation on MS medium +4.0 mg l(−1) 6-benzylaminopurine (BAP). Further shoot multiplication was achieved by repeated transfer of mother explants and subculturing of in vitro produced shoots on fresh medium. Maximum number (8.2 ± 0.17) of shoots were regenerated on MS medium with 1.0 mg l(−1) each of BAP and Kinetin (Kin) + 0.5 mg l(−1) α-naphthalene acetic acid (NAA) with additives (50 mg l(−1) of ascorbic acid and 25 mg l(−1) each of adenine sulphate, L-arginine and citric acid). The multiplied shoots rooted (4.3 ± 0.26 roots/shoot) on half strength MS medium with 2.5 mg l(−1) IBA. All the shoots were rooted ex vitro when pulse treated with 400 mg l(−1) of IBA for five min with an average of 7.3 ± 0.23 roots per shoot. Nearly 86 % of these plantlets were acclimatized within 7–8 weeks and successfully transferred in the field. Biologically significant developmental changes were observed during acclimation particularly in leaf micromorphology in terms of changes in stomata, veins and vein-islets, and trichomes. This study helps in understanding the response by the plants towards outer environmental conditions during acclimatization. This is the first report on micropropagation of C. guianensis, which could be used for the large-scale multiplication, restoration and conservation of germplasm of this threatened and medicinally important tree.